2015
DOI: 10.1002/ange.201502295
|View full text |Cite
|
Sign up to set email alerts
|

Following the Reaction of Heteroanions inside a {W18O56} Polyoxometalate Nanocage by NMR Spectroscopy and Mass Spectrometry

Abstract: , was isolated, in which the reaction of the two phosphite anions [HPO 3 ] 2À within the {W 18 O 56 } cage could be followed spectroscopically. As well as full X-ray crystallographic analysis, we studied the reactivity of the cluster using both solution-state NMR spectroscopy and mass spectrometry. These techniques show that the cluster undergoes a structural rearrangement in solution whereby the {HPO 3 } moieties dimerize to form a weakly interacting (O 3 PH···HPO 3 ) moiety. In the crystalline state the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, if hydrazine hydrate was not added during the synthesis, only "Trojan Horse" type clusters [W 18 O 56 (HPO 3 ) 2 (H 2 O) 2 ] 8- [7] formed as the exclusive product. Similarly, if sodium molybdate dihydrate was absent, the initially reduced solution of tungstate will…”
Section: Control Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, if hydrazine hydrate was not added during the synthesis, only "Trojan Horse" type clusters [W 18 O 56 (HPO 3 ) 2 (H 2 O) 2 ] 8- [7] formed as the exclusive product. Similarly, if sodium molybdate dihydrate was absent, the initially reduced solution of tungstate will…”
Section: Control Experimentsmentioning
confidence: 99%
“…Although multi-layered {M 30 O 90 } (M=W or Mo) clusters, incorporating both pyrophosphate and pyramidal HAs, have been reported, a general synthetic strategy is not yet developed for the assembly of such clusters based solely upon pyramidal HAs. [7] Scheme 1. Schematic representation of pyramidal heteroanion-directed and reduced Mo V -driven assembly of multi-layered POM cages.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…POMs are metal oxide cluster anions of V, Mo, and W in their highest oxidation states, which can be assembled from edge‐ and corner‐shared distorted MO 6 pseudo‐octahedral units to form a range of clusters with low to high nuclearities 12 . Due to the high number of stable isotopes of molybdenum ( 92 Mo, 14.84%; 94 Mo, 9.25%; 95 Mo, 15.92%; 96 Mo, 16.68%; 97 Mo, 9.55%; 98 Mo, 24.13%; 100 Mo, 9.63%), tungsten ( 180 W, 0.14%; 182 W, 26.53%; 183 W, 14.32%; 184 W, 30.68%; 186 W, 28.47%), and silicon ( 28 Si, 92.23%; 29 Si, 4.68%; 30 Si, 3.09%), high‐resolution mass spectrometry (HRMS) can precisely determine the cluster formula by matching the experimental vs calculated isotopic ion distributions 13,14 . For example, Cronin and co‐workers reported that electrospray ionization and cryospray mass spectrometry combined with high‐resolution time‐of‐flight systems could be applied to unravel the complexities of inorganic and supramolecular self‐assembly in solution 15 .…”
Section: Introductionmentioning
confidence: 99%